Application of coal-based carbon dots for photocatalysis and energy storage: a minireview. (9th September 2022) - Hou, Qinglin; Xing, Baolin; Guo, Hui; Kang, Weiwei; Yi, Guiyun; Cheng, Song; Zhang, Chuanxiang; Zhang, Yulong
Abstract : This review summarizes recent advances in coal-based carbon dots (CDs) from two perspectives, namely, the synthetic method and properties of CDs produced from different rank coals and the roles of coal-based CDs in applications of photocatalysis and energy storage. Abstract : Refined deep processing and utilization of high-value-added coal and transforming it into an enviro-friendly product is a pressing requirement to break the bottleneck of coal development. Carbon dots (CDs) are emerging as a new category of carbon nanomaterials that have attracted the attention of a growing group of researchers. A variety of coal-based CDs with different sizes, fluorescence and properties have been designed and constructed employing different rank coals and their derivatives as carbon sources. Due to their adjustable fluorescence emission, abundant surface defects, and electron-transfer efficiency, coal-based CDs have shown excellent and essential prospects in the catalysis and energy storage fields. Herein, this work overviews recent progress in research into coal-based CDs and emphasizes the synthetic methods and properties of CDs produced from different rank coals and coal tar pitch. This work focuses on their roles in boosting the applications of photocatalysis and energy storage. In addition, insights into future research exploration and challenges are presented. It is expected to stimulate researchers to design various efficient coal-based CD composites for photocatalysis and energy storage.